2018
DOI: 10.2967/jnumed.118.214833
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-Labeled Prostate-Specific Membrane Antigen Is a Novel PET/CT Tracer for Imaging of Hepatocellular Carcinoma: A Prospective Pilot Study

Abstract: Ga-Prostate Specific Membrane Antigen (Ga-PSMA), a positron emission tomography (PET) tracer that was recently introduce for imaging of prostate cancer, may accumulate in other solid tumors including Hepatocellular Carcinoma (HCC). The aim of the study was to assess the potential role of Ga-PSMA PET-Computed Tomography (CT) for imaging of HCC. A prospective pilot study in seven patients with HCC with 41 liver lesions: 37 suspected malignant lesions (tumor lesions) and 4 regenerative nodules. For each liver les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 23 publications
3
84
0
1
Order By: Relevance
“…One of these tumors is hepatocellular carcinoma. Only several case reports to date highlighted PSMA positivity of hepatocellular carcinoma on PET/CT [7][8][9][10]. Therefore, we provide here the first comprehensive evaluation of PSMA expression in HCC, benign peritumoral tissue and benign liver tumors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One of these tumors is hepatocellular carcinoma. Only several case reports to date highlighted PSMA positivity of hepatocellular carcinoma on PET/CT [7][8][9][10]. Therefore, we provide here the first comprehensive evaluation of PSMA expression in HCC, benign peritumoral tissue and benign liver tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Some of these tumors have already been extensively characterized with regard to PSMA expression (kidney cancer, breast cancer, gastric cancer, colon cancer), others are still not addressed (hepatocellular carcinoma, endometrial cancer). Several case reports and one case series to date reported the positivity at PSMA positron emission tomography / computed tomography (PET / CT) in approximately 10 patients with a hepatocellular carcinoma (HCC) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] PSMA uptake has been randomly reported in cases of colon, esophageal, thyroid, lung, and liver cancers, intrahepatic cholangiocarcinoma, renal cell carcinoma, brain tumors, sarcoidosis, Paget bone disease, rib fractures, and so on. [ 10 12 ] Kesler M et al performed 68 Ga-PSMA PET/CT imaging on 41 lesions in 7 patients suspected of having HCC [ 13 ] and reported that 68 Ga-PSMA positivity was detected in 36/37 tumor lesions. They also found that none of the 4 regenerative nodules examined showed an increase in 68 Ga-PSMA uptake.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 55 articles were extrapolated with the computer literature search and by reviewing the titles and abstracts 43 of them were excluded because the reported data were not within the field of interest of this review. Twelve articles were selected and retrieved in full-text version [22][23][24][25][26][27][28][29][30][31][32][33]; one additional study was found screening the references of these articles [34]. A total of 13 articles were then included in the systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34] (Fig.…”
Section: Literature Searchmentioning
confidence: 99%